Naturally Occurring Exosome Vesicles as Potential Delivery Vehicle for Bioactive Compounds - Akuma, Precious; Okagu, Ogadimma D.; Udenigwe, Chibuike C. (Frontiers in Sustainable Food Systems, 2019)
Various kinds of vesicles have been produced from plant, animal and inorganic materials for use as delivery vehicles especially in functional food formulation. However, major drawbacks associated with most of them include issues with sustainability, safety, biocompatibility, biorecognition, stability, bioavailability, bioadhesion, generation of reactive species, inefficient encapsulation and protection, and inability to release the bioactive compounds at target regions of the gastrointestinal tract. The use of vesicles innately formed in plant and animal cells as delivery agents would potentially solve most problems associated with the existing nanodelivery systems. Underutilized vesicles, known as exosomes, exist in plant and animal cells, where they play roles in cell communication and nutrient delivery. To date, exosomes have proven to be stable, biocompatible and able to withstand the activity of digestive enzymes until they reach their target locations. However, there is a need to explore better ways of inducing exosome production, to elucidate their physiological roles, and understand their biogenesis in plants, to discover sustainable methods of isolation of high yields of the vesicles. There is also a need to clarify the digestibility and interaction of the exosomes with blood and gastrointestinal fluids. This review highlights the isolation techniques and delivery potential of exosomes, and equally presents research gaps for enhancing the use of the natural vesicles for delivery purposes.